Prospects for Africa's economic growth - Przemyslaw Cieslak (Institute of Economic Research (IER), 2016)
On the African continent for a decade is observed economic growth, combined with the demographic explosion. In the XXI century countries which have been given the nickname of the Third World have a chance to offset the distance of the level of socio-economic development with the rest of the world, and at the same time become the next, after Asia, center of dynamic economic growth. Based on the theory of convergence, the analysis of economic ties between African countries and the developed economies such as the United States, European Union, Australia, Japan, and the fast developing as China and Brazil a decade ago was conducted. The analysis made it possible to shift the dynamics of growth in GDP per capita in the years 1960-1995 in developed countries to six African countries, including Algeria, Angola, Kenya, Mozambique, Nigeria, and South Africa. On this basis, we obtained the forecast of gross domestic product (GDP) per capita in these countries till 2030.
Keywords: C15; C53; N27; O11; 330; economic growth; Africa; forecasting and simulation; macroeconomic analyses of economic development; cluster analysis